Natural yeast flora of different varieties of grapes used for wine making in India - Chavan, Pradnya; Mane, Sarika; Kulkarni, Girish; Shaikh, Shamim; Ghormade, Vandana; Nerkar, Devidas P.; Shouche, Yogesh; Deshpande, Mukund V. (Food Microbiology, 2009)
The natural Saccharomyces and non-Saccharomyces yeast flora present on the grape berries significantly affect wine production. Six grape varieties, Bangalore blue, Zinfandel, Cabernet, Chenin Blanc, Sauvignon Blanc and Shiraz are being used in India for wine making. The yeast diversity was studied on the basis of morphological, colony, physiological characteristics and 5.8S-ITS sequencing of rDNA of the isolates. Eleven different species belonging to seven genera were identified as: Candida azyma, Candida quercitrusa, Debaryomyces hansenii, Hanseniaspora guilliermondii, Hanseniaspora viniae, Hanseniaspora uvarum. Issatchenkia orientalis, Issatchenkia terricola, Pichia membranifaciens, Saccharomyces cerevisiae and Zygoascus steatolyticus. H. guilliermondii was the predominant species while S. cerevisiae was observed occasionally in the six vine varieties. For the first time, C. azyma was isolated from Bangalore blue and Cabernet varieties grown in different localities. This association may be attributed to the change in cropping pattern from sugarcane to viticulture in the vine growing regions and the known association of C. azyma with sugarcane phylloplane. Further analysis of the indigenous strains and the qualitative and quantitative changes in the flora during fermentation will be useful to understand wine quality and to design preservation strategies to control wine spoilage. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 5.8S-ITS sequence; Identification; Physiological; Wine yeasts